Penyelesaian Sengketa Tanah Petuanan Antara Marga Walalayo Negeri Hatu Dan Negeri Saunulu Kecamatan Tehoru Kabupaten Maluku Tengah - Walalayo, Isabella; Laturette, Adonia Ivonne; Radjawane, Pieter (PATTIMURA Law Study Review, 2024)
The rights of a legal partnership over the land around its environment are known as Ulayat Rights which is the highest right to land owned by a legal association (Tribe, State, or Village) where the members of the community (legal association) have the right to control it and in its implementation it is regulated by the heads of the alliance (Tribal Head, King or Village Head) concerned. This research aims to examine the regulation of customary rights land boundaries according to customary law and how to resolve disputes over clan land rights that border between one country and another. The research method used is a type of Normative Legal research, namely library research or document study. The results of this research show that resolution of a dispute can be done in two ways, namely through litigation (in court) and through non-litigation (outside court). Based on the results of the author's research, historically the ownership of customary rights controlled by the Walalayo clan of Negeri Hatu has existed since the time of the ancestors from 1620, but in 2016 the people of Negeri Hatu planned to clear the land to make plantations but this was prohibited by the Sounolu State because the Sounolu State through the Chief The village claimed that the customary rights belonged to them because this ultimately resulted in a dispute and led to conflict between the two countries. In resolving the dispute in question, it was resolved through mediation through the Central Maluku Regency Police Department until there was a judge's decision regarding the resolution of the dispute, but both parties still maintain their respective rights so that to date the dispute over the owner of the customary land has not been resolved.